MASSIVE HAEMORRHAGE IN PATIENT AFTER REPAIR OF POST ESOPHAGECTOMY DIAPHRAGMATIC HERNIA AND A LOADING DOSE OF CLOPIDOGREL - Saleem, Huma; Malik, Sara Haider; Mehdi, Syed Raza (Journal of Ayub Medical College Abbottabad, 2018)
Postoperative diaphragmatic hernia (PDH) is an increasingly reported complication of esophageal cancer surgery. It occurs more frequently with minimally invasive techniques and very little is known about its pathogenesis. Currently, no consensus exists concerning preventive measures and its management. A 36 years old male underwent minimally invasive esophagectomy and presented with chest pain and dyspnoea in the emergency department 8 months after the procedure. He was started on acute coronary syndrome treatment protocol but was later diagnosed on CT scan to have diaphragmatic hernia through a defect in the oesophageal hiatus. As he was already loaded with dual anti platelet therapy it led to qualitative defect of the platelet which resulted in bleeding post procedure and the patient needed resuscitation with blood products. Dual anti-platelet therapy is an integral component of early management strategy in acute coronary syndrome. Chest X-ray was not helpful, but abdominal or chest computed tomography was useful for accurate diagnosis. Keywords: massive haemorrhage; esophagectomy; diaphragmatic hernia; dual anti platelet therapy